Osteogenic Differentiation and Biocompatibility of Bovine Teeth Scaffold with Rat Adipose-derived Mesenchymal Stem Cells - Sari, Desi Sandra; Maduratna, Ernie; Ferdiansyah; Latief, Fourier Dzar Eljabbar; Satuman; Nugraha, Alexander Patera; Sudiana, Ketut; Rantam, Fedik Abdul (European Journal of Dentistry, 2019)
Objective Adipose-derived mesenchymal stem cells (ADMSCs) have great potential for regenerative medicine. These have been combined with biomaterials such as Bovine teeth that are preferred as a periodontal regeneration material. The main purpose of this study is to evaluate and analyze a biocompatibility test and osteogenic differentiation of bovine teeth scaffold seeded with ADMSCs in vitro.Materials and Methods A true experimental study with post-test only group design was conducted. Random sampling and Lameshow's formula were used to determine the sample. The scaffold, obtained from bovine teeth as the bone graft material, was analyzed using 3- (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and its attachment was evaluated by scanning electron microcopy (SEM) and micro-computed tomography with ADMSCs. ADMDSCs attachment present in the bovine teeth scaffold was assessed using SEM at 1-hour, 12-hour, and 24-hour intervals.Statistical Analysis Analysis of variance was used to analyze the MTT assay results (p < 0.05) based on normality and homogeneity test (p > 0.05).Results The highest viability of cells (97.08%) was found at a concentration of 10% by means of an MTT test (p < 0.05). The results of three-dimensional bovine teeth scaffold showed the average particle size to be 500 µm. ADMSCs cell attachment to the scaffold bovine teeth showed a significant increase in the number of cells attached after 24 hours compared with those at 1 and 12 hours. Alizarin red staining showed an increase in ADMSC osteogenic differentiation after it was combined with bovine teeth scaffold.Conclusion The scaffold from bovine teeth is biocompatible and accelerates osteogenic differentiation of ADMSC.
Keywords: adipose-derived mesenchymal stem cells; bovine teeth; scaffold; tissue engineering